Encouraging a Market in Human Milk - Waldeck, Sarah E. (Columbia Journal of Gender and Law, 2002)
Although economics teachers never invoke the metaphor of a lactating breast, it nicely illustrates a natural equilibrium between supply and demand. The more a baby sucks or a mother pumps, the more milk the breast produces. This is why a mother comfortably nurses an infant who doubles and then triples his weight during the first twelve months; it is why a woman can successfully nurse twins and even triplets. It is also the biological foundation for my central premise: that our legal regime should encourage a market in human milk-the superior source of infant nutrition. Ever since medical technology has allowed humans to share blood, organs and other tissue, discussion has raged about the practical and ethical implications of commercializing products of the human body. Breastmilk, however, is rarely mentioned in the course of the debate. This silence is curious, especially since babies have always consumed milk from women other than their biological mothers. Until the advent of infant formula, wet nursing was the only way to save an infant whose mother had died or was unavailable. Even today informal sharing of milk continues, although the Centers for Disease Control and Prevention recommends against it. Some mothers nurse another woman’s child when babysitting. More commonly, women pump milk for the child of a friend or relative, typically because the child is adopted and the adoptive mother is not lactating.